Adenine base editing of the DUX4 polyadenylation signal for targeted genetic therapy in facioscapulohumeral muscular dystrophy - Darina Šikrová; Vlad A. Cadar; Yavuz Ariyurek; Jeroen F.J. Laros; Judit Balog; Silvère M. van der Maarel (Elsevier, 2021)
Facioscapulohumeral muscular dystrophy (FSHD) is caused by chromatin relaxation of the D4Z4 repeat resulting in misexpression of the D4Z4-encoded DUX4 gene in skeletal muscle. One of the key genetic requirements for the stable production of full-length DUX4 mRNA in skeletal muscle is a functional polyadenylation signal (ATTAAA) in exon three of DUX4 that is used in somatic cells. Base editors hold great promise to treat DNA lesions underlying genetic diseases through their ability to carry out specific and rapid nucleotide mutagenesis even in postmitotic cells such as skeletal muscle. In this study, we present a simple and straightforward strategy for mutagenesis of the somatic DUX4 polyadenylation signal by adenine base editing in immortalized myoblasts derived from independent FSHD-affected individuals. We show that mutating this critical cis-regulatory element results in downregulation of DUX4 mRNA and its direct transcriptional target genes. Our findings identify the somatic DUX4 polyadenylation signal as a therapeutic target and represent the first step toward clinical application of the CRISPR-Cas9 base editing platform for FSHD gene therapy.